PENDAMPINGAN PEMBERIAN MPASI PUDING LABU DALAM UPAYA MENCEGAH TERJADINYA STUNTING PADA ANAK - Nina Hidayatunnikmah; Novi Rahmawati; Salsa Rifqah Nuraini; Endang Tri Arsita Setyani; Rivana Ardyanti Aulia; Dini Anggraini; Maria Rosalina Fono; Yulita Gunu Ritan; Alya Da Silva; Umi Maulidiyatur Rochmawati; Rafasha Hajarikhfar (LP2M Universitas Ibrahimy, 2024)
Stunting is one of the priorities in Gading Village. Several attempts have been made to overcome this problem, such as providing highly nutritious food ingredients to stunted toddlers. However, in 2023 there was an increase in the number of stunting to 9 toddlers. Even when the Posyandu was held in August there were approximately 14 toddlers who were stunted. For this reason, efforts to eradicate stunting must continue. One of them is by giving MPASI to toddlers during the posyandu. One of the MPASI that is suitable for this purpose is processed pumpkin. The processed product we chose was to make pumpkin pudding. Methode that was used in the activity is Participatory Action Research (PAR) where both KKN team and the posyandu community are actively working together. Community service activities were carried out on 9-11 August 2023. This activity provided MPASI and posters that were well-welcomed by the community. It can be seen from the huge number of toddlers who attended the activity at that time. Also, from the data that have been collected we know that about 14 toddlers are stunting.